Episotology of Ovarian Hypofunction in Cows (Literature Analysis) - B.T. Sidikov; K.A. Mirzakasimova (Genius Journals, 2022)
This article analyzes the causes, clinic, course and diagnosis of ovarian hypofunction on the basis of literature data.
Keywords: Ovary; hypofunction; cletchatka; subinvoliction